Valorization of crude glycerol into hydrogen, 1, 3-propanediol, and ethanol in an up-flow anaerobic sludge blanket (UASB) reactor under thermophilic conditions. (December 2020) - Sittijunda, Sureewan; Reungsang, Alissara
Abstract: Simultaneous hydrogen, ethanol, and 1, 3-propanediol (1, 3-PD) production from pure and crude glycerol were performed under thermophilic conditions (55 ± 4 °C). The effect of the organic loading rate (25, 37.5, 50, 62.5, and 75 g/L-d) on the formation of hydrogen, ethanol, and 1, 3-PD was investigated. Maximum hydrogen yields of 2.90 and 2.05 mol-H2 /mol-glycerol were achieved with OLR of 62.5 g/L-d of pure and crude glycerol. 1, 3-PD yields of 0.32, 0.36 mol/mol-glycerol and ethanol yields of 0.19, 0.22 mol/mol-glycerol were achieved with the optimum OLRs using pure and crude glycerol. Ethanol production at 50.77 and 51.09 mmol/L was achieved at OLRs of 37.5 and 75 g/L-d, respectively, using pure and crude glycerol as substrates while the hydrogen and 1, 3-PD yields of 1.08 and 1.69 mol-H2 /mol-glycerol and 0.32 and 0.36 mol/mol-glycerol were obtained from these optimal OLRs. COD balance under optimum OLR using pure and crude glycerol as the substrate indicates that 1, 3-PD and hydrogen were the main products followed by ethanol. The energy conversion efficiency for hydrogen, 1, 3-PD, and ethanol was 34.87, 39.54, 17.88%, respectively. Enterobacter sp., Klebsiella sp., and K. pneumoniae, were found as the simultaneous hydrogen, ethanol, and 1, 3-PD producing bacteria presence in pure and crude glycerol fermentation. Graphical abstract: Image 1 Highlights: H2, EtOH, 1, 3-PD were produced from crude glycerol under thermophilic conditions. UASB reactor was operated at OLRs of 50, 62.5, and 75 g/L-d. H2, 1, 3-PD, and EtOH achieve 92.29% energy conversion efficiency. Enterobacter sp., Klebsiella sp . produced H2, 1, 3-PD, and EtOH simultaneously. Changing OLR influences the NADH/NAD + ratio which resulted in variety of products.